FROM BIOMECHANICS TO NOCIPLASTICITY: RESTRUCTURING CLINICAL REASONING IN THE REHABILITATION OF TRAUMATIC CERVICAL SPINAL CORD INJURY - Rogério da Silva Rocha (Artefactum - revista de estudos interdisciplinares, 2026)
Traumatic cervical spinal cord injury is one of the most severe neurological conditions in modern clinical practice, resulting in profound motor, sensory, autonomic, respiratory, functional, and psychosocial impairments. Advances in neuroscience have significantly transformed the understanding of chronic pain, neuroplasticity, and functional recovery following central nervous system injuries. Consequently, contemporary physical therapy has evolved beyond a purely biomechanical perspective, incorporating concepts related to nociplastic pain, central sensitization, adaptive neuroplasticity, and evidence-based rehabilitation. This study aims to discuss the neurobiological foundations of pain and rehabilitation in patients with complete traumatic cervical spinal cord injury, integrating current pain neuroscience concepts with the clinical analysis of a complex neurological case. This work consists of a clinical case report combined with an integrative literature review. The patient was a 54-year-old male involved in a motorcycle accident in April 2026, resulting in cervical fracture, traumatic cervical myelopathy, complete spinal cord injury, tetraplegia, grade zero muscle strength, complete functional dependence, and a guarded neurological prognosis. The analysis demonstrates that although neurological recovery remains limited in complete spinal cord injuries, specialized physical therapy plays a crucial role in preventing secondary complications, preserving residual function, managing pain, optimizing quality of life, and providing biopsychosocial support. The findings reinforce the importance of a multidimensional patient-centered approach grounded in contemporary neuroscience and evidence-based practice.